Influence of the Polyphenol extracts from apple skin on the viability of Probiotic bacteria in model milk drink - Shinde, T; Brooks, JD; Sun-Waterhouse, D (The University of Auckland, 2011)
Functional foods and ingredients present health-promoting benefits to the consumers beyond normal nutrition. Functional foods containing polyphenol antioxidants and probiotic bacteria are especially gaining increased market leverage. Therapeutic manipulation of gut microflora with probiotics promises to be a useful strategy for several disorders, including infectious and inflammatory conditions. Probiotic bacteria however, exhibit low viability in dairy foods during storage, owing to the low pH and oxidative stress generated during processing. The low viability subsequently affects the ability of probiotic bacteria to impart their desired health benefits. Polyphenol antioxidants can reduce the oxidative stress in the food system, which in turn may influence the survival of probiotic bacteria in the food. The objective of this study was to investigate the functional attributes of apple skin polyphenols towards the survival of probiotic bacteria in a model fruit extract-enhanced milk drink. The influence of apple skin polyphenols (extracted using either ethanol or citric acid infused water), on the survival of Lactobacillus acidophilus in milk was examined over 30 days under refrigeration. The viability of L. acidophilus was higher in milk enhanced with both apple skin polyphenol extracts than in milk only (control), with the viability of L. acidophilus being marginally higher for the milk enhanced with acidic water polyphenol extract. Thus, apple skin may be a potential source of polyphenols which can be used as bioactive food ingredients to maintain the viability of probiotic bacteria in dairy products. Future work will optimise the delivery of both polyphenols and probiotic bacteria, including the use of a microencapsulation technique to preserve these bioactives in the final model milk drink systems.
Keywords: Functional Food; Probiotic